KONFLIK OTORITAS, KEKUASAAN DAN KELOMPOK KEPENTINGAN DI PERUSAHAAN PERKEBUNAN : Studi pada PT. Musirawas Citraharpindo di Kabupaten Seruyan - Jhon Roy Purba; Joni Rusmanto (Journal SOSIOLOGI, 2021)
This thesis is titled Conflict of Authority, Power and Interest Group of Oil Palm Plantation Companies (Study at PT. Musirawas Citraharpindo in Perspective of Conflict of IndustrialSociety RALF DAHRENDORF). The purpose of this thesis research is to examine and explain the system of authority, power and interest groups of PT. Musirawas Citraharpindo, as well as researching and explaining the authority and power in leadership can affect the emergence of internal conflict PT. Musirawas Citraharpindo. In this study, the approach used by researchers is qualitative approach by conducting direct observation in the field and conducting interviews to PT employees. Musirawas Citraharpindo, recorded the observations and results of interviews and documentation on the grounds that researchers wanted to dig up information, collect data, analyze data and conclude how corporate authority, power, and interest groups and how authority and leadership power affect the dynamics of internal conflicts of the company.Based on the results of research on authority, power and interest groups in PT. Musirawas Citraharpindo was awakened as a result of the dominant role and position of a person who was then used as a regulator and controller to every employee, especially small employees who worked on the plantation. In addition, the conflict in PT. Musirawas Citraharindo was awakened by labor dissatisfaction both individually and collectively that was not organized in fighting for interests and achieving a goal.